An Analysis of Types of Directive Acts Found in â€œThe School for Good and Evilâ€ Movie - Selva New Puspita Naibaho; Robby Satria (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study has purpose to find the types of directive acts that performed by the characters in â€œThe School for Good and Evilâ€ movie. This research is descriptive qualitative research. This research used a theory proposed by Searle and Vanderveken (1985). This study used observational and a non-participatory technique of data collection. This research also used referential identity method and the pragmatic competence technique in equalizing in analysing the data. There are some steps in the process of collecting the data. Firstly, the researchers watched the data source which is â€œThe School for Good and Evilâ€ movie. Secondly, the researchers downloaded the script of the movie. The researchers then watched the movie and read the script in the exact same time. Finally, the researchers marked the utterances that showed the directive acts. The result showed that there were 17 data of directive acts performed by the characters in â€œThe School for Good and Evilâ€ movie. There were 8 data of asking type, 1 data of permitting type, 2 data of ordering type, 1 data of requesting type, 1 data of commanding type, 2 data of inviting type, and 2 data of advising type. Eventually, â€œThe School for Good and Evilâ€ movie characters most frequently use the asking type of directive acts.